Automobile compression composite elliptic spring - Goudah, G.; Mahdi, El-Sadig; Abu Talib, Abd Rahim; Mokhtar, A. S.; Yunus, Robiah (Federation of Engineering Institutions of Islamic Countries, 2006)
An automotive suspension system is designed to provide both safety and comfort for the occupants. When a vehicle encounters a road surface irregularity, the tire deforms and the suspension displaces. Some of the energy caused by the disturbance is dissipated in the tire, while in the old design, some energy is dissipated in the shock absorber and the remainder of the energy is stored in the coil spring. In this paper, Finite element models were developed to optimize the material and geometry of the composite elliptical spring based on the spring rate, log life and shear stress. The influence of ellipticity ratio on performance of woven roving wrapped composite elliptical springs has been investigated both experimentally and numerically, this study demonstrated that composites elliptical spring can be used for light and heavy trucks and meet the requirements, together with substantial weight saving. The results showed that the ellipticity ratio significantly influenced the design parameters. Composite elliptic spring with ellipticity ratios of a/b 2 displayed the optimum spring model.